ASSOCIATION OF GENDER AND TOOTH LOSS DUE TO DENTAL CARIES - A RETROSPECTIVE STUDY - PRATHA, A.ASHWATHA; BALASUBRAMANIAM, ARTHI; JAIN, RAVINDRA KUMAR (The journal of contemporary issues in business and government, 2021)
The retention or loss of permanent teeth is of central importance to an individual's oral health status and to qualify for life. Prevalence of tooth loss and dental caries has been documented more among women than in men in many parts of the world. Smoking habits more performed by men had increased chance of development of dental caries progressively leading to tooth loss. Thus this study aimed to find association of gender and tooth loss. This retrospective study was conducted using records of patients visited private Dental College. A total of 644 consecutive case records of patient age ranging from 20-90 years were retrieved. Data on the number of missing teeth due to caries from their records were entered and subjected to statistical analysis. Descriptive statistics was done to present the prevalence of missing teeth. Chi-square association was performed to find the association. Among the patients 53.88% males and 38.04% females had one tooth loss due to caries. About 0.93% of patients in age group 41-60 years, 0.78% in age group 20-40 years had four missing teeth due to caries. A significant association exists between age groups and missing teeth due to caries (p<0.05) whereas no significant association was observed between gender and missing teeth due to caries. Within the limits of the study, prevalence of tooth loss due to caries is higher in males compared to females with insignificant association.